Immunomodulator drug-based therapy in myeloma and the occurrence of thrombosis. Issue 6 (December 2012) - Boyle, Eileen M; Fouquet, Guillemette; Manier, Salomon; Gauthier, Jordan; Noel, Marie Pierre; Borie, Claire; Facon, Thierry; Elalamy, Ismail; Leleu, Xavier
Immunomodulator drugs (IMiDs) have contributed to the significant improvement observed in the survival of myeloma patients since the introduction of novel targeted therapies. The introduction of IMiDs in the myeloma pipeline has also significantly increased the incidence rate of thromboembolic events, either venous and/or arterial. The observation of an increasing number of deep venous thrombosis makes it compulsory to discuss prophylactic options in myeloma, particularly in those treated with IMiDs as immunomodulatory drugs. Although an attempt to propose guidelines was performed, it is clear that several questions remain unanswered, starting with the choice of the thromboprophylaxis and the definition of risk factors. We have reviewed evidence that might help to decide the optimal thromboprophylaxis, and also highlighted the unresolved area where further study is warranted.